Pelanggaran Prinsip Kerja Sama Dalam Film “Kisah Nabi Yusuf” Episode 18 Pada Kanal Youtube Salam Media (Kajian Pragmatik) - Hopi Silviani Hopi Silviani; Maman Abdul Djaliel; Dayudin (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2025)
This study aims to analyze violations of the Cooperative Principle in Kisah Nabi Yusuf AS Episode 18, which was broadcast on the Salam Media YouTube channel. The research employs a qualitative descriptive method with a pragmatic approach, focusing on the identification and classification of Cooperative Principle violations based on Grice’s theory, namely the maxims of quantity, quality, relevance, and manner. The research data consist of utterances produced by the characters in the film, collected through observation and note-taking techniques. Data analysis was conducted by applying intralingual and extralingual matching techniques to interpret the utterances in relation to their linguistic and situational contexts. The findings reveal that violations of all four maxims of the Cooperative Principle occur in the dialogues between characters, serving various communicative purposes such as avoiding direct responses, concealing particular intentions, conveying implicit meanings, and enhancing the dramatic effect of the narrative. These findings indicate that violations of the Cooperative Principle function as pragmatic strategies that support interactional dynamics and conflict development within film discourse.